2017
DOI: 10.3390/jcm6020019
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Seeking Help for Skin Cancer Detection in Rural Australia

Abstract: This study explores rural South Australians’ barriers to help-seeking for skin cancer detection. A total of 201 randomly selected rural adults (18–94 years, 66% female) were presented with a skin-cancer-related scenario via telephone and were asked the extent to which various barriers would impede their help-seeking, based on an amended version of the Barriers to Help-Seeking Scale. Older (≥63 years) and less educated participants endorsed barriers more strongly than their younger, more educated counterparts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 32 publications
0
43
1
Order By: Relevance
“…Differences in cancer incidence and help-seeking between urban and rural environments may be due to aforementioned access difficulties, as well as cultural factors. These include occupational differences, unique attitudes towards health and help-seeking found among people living in rural areas (Emery et al, 2013;Fennell et al, 2017), and hegemonic rural masculinity (Alston & Kent, 2008;Courtenay, 2000). In the case of the latter, conformity to dominant rural masculinity positions men as hard working, physically tough, self-reliant, and stoic (Alston & Kent, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in cancer incidence and help-seeking between urban and rural environments may be due to aforementioned access difficulties, as well as cultural factors. These include occupational differences, unique attitudes towards health and help-seeking found among people living in rural areas (Emery et al, 2013;Fennell et al, 2017), and hegemonic rural masculinity (Alston & Kent, 2008;Courtenay, 2000). In the case of the latter, conformity to dominant rural masculinity positions men as hard working, physically tough, self-reliant, and stoic (Alston & Kent, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Emery et al (2013) and Fennell et al (2017) found aspects of rural identity, including optimism, stoicism, machismo, and self-reliance contributed to rural men's delayed help-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Fennell et al reported being older (>63 years) and less educated were barriers for people seeking help for skin cancer detection in rural Australia. 22 The majority of participants in the current study agreed that patient education, continuing medical education of GPs and registrars on skin cancer, and having effective recall systems were important to improve skin cancer follow-up. Based on the findings, it would be beneficial for rural GPs to review and/or establish follow-up strategies suited to rural populations for both NMSC and melanoma skin cancers.…”
Section: Discussionmentioning
confidence: 77%
“…Help‐seeking behaviour is a term which is used in different contexts. Its most commonly used surrogate terms in the context of cancer are seeking help 23,24, seeking medical help 25,26 and medical help‐seeking 9,27.…”
Section: Resultsmentioning
confidence: 99%
“…Correct interpretation of symptoms and their attribution to cancer are facilitators to HSB (3,13,40), while misinterpretation of symptoms and their attribution to normal conditions or benign problems are barriers to HSB (15,37,41,42). Moreover, old age (16,(43)(44)(45), young age (23,28,32,33), marriage (46,47), low education level (16,27,37), positive family history of cancer (39,(48)(49)(50), fear over cancer (10,15,39,51), low perceived threat (3,15) and symptom disclosure to significant others (7,15,48,52) can act as both facilitators and barriers to HSB ( Table 1).…”
Section: Antecedentsmentioning
confidence: 99%